Vitamin D deficiency is associated with greater tumor size and poorer outcome in Merkel cell carcinoma patients. (1st February 2013) - Samimi, M.; Touzé, A.; Laude, H.; Le, E.; Arnold, F.; Carpentier, A.; Gardair, C.; Carlotti, A.; Maubec, E.; Dupin, N.; Aubin, F.; Avril, M.F.; et al.
Abstract Background Merkel cell polyomavirus has been recognized to be associated with Merkel cell carcinoma (MCC), but the evolution of this cancer probably depends on various factors. Vitamin D deficiency, defined by serum 25‐hydroxyvitamin D levels <50 nmol/L, seems to influence cancer behavior and progression, but has never been assessed in MCC patients. Objectives First, to evaluate whether vitamin D deficiency was associated with tumor characteristics and prognosis in a cohort of MCC patients. Second, to assess expression of the vitamin D receptor (VDR) in MCC tumors. Methods Clinical findings, Merkel cell polyomavirus markers and vitamin D status were assessed in a cohort of French MCC patients. The study was limited to the 89 patients for whom the serum sample had been collected within 3 years after the diagnosis of MCC. Correlation between vitamin D deficiency and MCC characteristics and outcome were determined in regression analyses. VDR expression in MCC tumours was assessed by immunohistochemistry. Results Vitamin D deficiency was noted in 65.1% of the patients and was independently associated with greater tumor size at diagnosis (P = 0.006) and with metastasis recurrence (HR, 2.89; 95% CI, 1.03 to 8.13; P = 0.043), but not with death from MCC, although there was a trend (HR, 5.28; 95% CI, 0.75 to 36.96; P = 0.093). VDR was found to be strongly expressed in all 28 MCC tumor specimens investigated. Conclusion The association between vitamin D deficiency and MCC characteristics and outcome, together with detection of the VDR in MCC cells, suggest that vitamin D could influence the biology of MCC.